J.K. Lasser's 1001 deductions and tax breaks 2026 : your complete guide to everything deductible - Weltman, Barbara (John Wiley & Sons, Inc., 2026)
In the newly revised edition of J.K. Lasser's 1001 Deductions and Tax Breaks 2026: Your Complete Guide to Everything Deductible, renowned tax expert Barbara Weltman walks you through every relevant tax credit and deduction you're entitled to claim on your 2025 return, including brand new tax breaks introduced just this year. You'll find hundreds of money-saving opportunities that help ensure you don't overpay on your taxes, giving Uncle Sam exactly what you're legally required to give him -- and not a penny more!